2022
DOI: 10.1371/journal.pone.0262540
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the potential geographical distribution of Betula platyphylla Suk. in China under climate change scenarios

Abstract: Climate is a dominant factor affecting the potential geographical distribution of species. Understanding the impact of climate change on the potential geographic distribution of species, which is of great significance to the exploitation, utilization, and protection of resources, as well as ecologically sustainable development. Betula platyphylla Suk. is one of the most widely distributed temperate deciduous tree species in East Asia and has important economic and ecological value. Based on 231 species distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Furthermore, with the intensifying global warming, the suitable area for C. luteoflora began to gradually become fragmented as it shifted to higher latitudes and altitudes. Other plants species ' Climate is the dominant factor affecting the geographical distribution of species at large scales in geographic regions [47]. Dai et al concluded that mainly the mean temperature of the warmest quarter, precipitation of the warmest quarter, and precipitation of the coldest quarter were the dominant factors affecting the potential geographical distribution of C. luteoflora.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, with the intensifying global warming, the suitable area for C. luteoflora began to gradually become fragmented as it shifted to higher latitudes and altitudes. Other plants species ' Climate is the dominant factor affecting the geographical distribution of species at large scales in geographic regions [47]. Dai et al concluded that mainly the mean temperature of the warmest quarter, precipitation of the warmest quarter, and precipitation of the coldest quarter were the dominant factors affecting the potential geographical distribution of C. luteoflora.…”
Section: Discussionmentioning
confidence: 99%
“…Since only CCSM4, MIROC–ESM and MPI–ESM–P Global Climate Models (GCMs) were available for the data of the LGM, to compare the prediction results of different GCMs, we selected the above three GCMs to simulate the ancient distribution of Polyspora . CCSM4 (The Community Climate System Model version 4) (Gent et al, 2011 ) is one of the most effective GCMs for predicting the impact of climate change on the distribution of animal and plant (Geng et al, 2022 ), and has the best precipitation prediction performance (Yang et al, 2020 ), especially for the precipitation prediction in southwest China (Yang, Yong, et al, 2021 ). MIROC–ESM (the Model for Interdisciplinary Research on Climate Earth System Model) has a good simulation of terrestrial carbon cycle and vegetation dynamics (Watanabe et al, 2011 ), and a good prediction of rainfall in the Yangtze River basin of China (Yang et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…LGM, to compare the prediction results of different GCMs, we selected the above three GCMs to simulate the ancient distribution of Polyspora. CCSM4 (The Community Climate System Model version 4) (Gent et al, 2011) is one of the most effective GCMs for predicting the impact of climate change on the distribution of animal and plant (Geng et al, 2022), and has the best precipitation prediction performance (Yang et al, 2020), especially for the precipitation prediction in southwest China (Yang, Yong, et al, 2021) is a model specially designed for paleoclimate simulation (Braconnot et al, 2012;Jungclaus et al, 2013), which is accurate in simulating the trend of extreme temperature change in China (Jiang et al, 2017).…”
Section: Environmental Datamentioning
confidence: 99%
“…We understood the spatial autocorrelation to be due to overfitting of the data results caused by an overdense sample size in some regions 45 . These operations can greatly reduce the spatial autocorrelation of species occurrence data and effectively reduce the error 46 . Finally, data from 2529 samples of C. sinensis , C. cicadae , C. militaris and C. gunnii were obtained (Fig.…”
Section: Methodsmentioning
confidence: 99%